Järvhonors rörelsemönster kring lyplatsen under lyperioden - Thomasdotter Myhr, Tove-Mathilda (SLU/Dept. of Animal Environment and Health (until 231231), 2015)
The wolverine is the world’s largest mustelids and is both a carnivore and a scavenger. In Sweden wolverines occur in the mountains and coniferous forests from the northern parts down to south-central Sweden. In the reindeer husbandry area its main food is reindeer (Rangifer tarandus) and outside the reindeer husbandry area they primarily scavenge remains from the moose hunt and wolf-killed moose. Wolverine females give birth to cubs in February or March in a den dug into a large snowdrift if the den is located in the mountain region and in the snow next to boulders if the den is located in the forest. The cubs suckle for about 10 weeks before they begin to eat meat. The female moves her cubs from the primary den, where the cubs are born, to secondary dens after a period. The cubs spend their time in the secondary den while the female is foraging and marking her territory. The aim of this study was to examine how the movement pattern of female wolverines looks like around the den during the denning period. A new method based on the use of camera stations have been proven to work for the documentation of wolverine presence in general, but also for documentation of lactating females (i.e. reproducing females). My thought with this study was that the knowledge about movement pattern of female wolverines during the denning period could be used to improve the efficiency in the use of camera stations for documentation of wolverine females in areas with poor conditions for snow tracking with focus on lactating wolverine females. The goal of this study was that the results would contribute to increased chances that camera stations are located where the wolverine female with a high probability will find and visit it based on her movement patterns when there is a suspected den site or knowledge of frequently used dens from previous years. The study is aimed at wildlife managers responsible for- and performing monitoring of wolverines. The study was conducted with position data from reproducing wolverine females equipped ...